Gestión administrativa de la Farmacia Tu Ahorro - Veloz Troya, Abner Adrian (2021)
The present investigative work aims to analyze and identify the situations that are happening in the pharmacies "TU AHORRO" which is dedicated to the sale of medical supplies and for this, the types of research such as exploratory and descriptive were used, methods such as deductive and inductive, techniques such as direct observation and interview, also the instruments used were the observation sheet and the questionnaire. This will allow knowing how the company is managed and with the administrative management will help to obtain satisfactory and acceptable results so that the management can efficiently and effectively take advantage of both technical, financial and human resources. This will help to diagnose the state of the administrative processes of the pharmacies "YOUR SAVINGS", and in turn will allow us to determine the areas to apply improvements within the company that will allow us to develop administrative strategies that help and improve the management of pharmacies and for this work, different sources about administrative management were consulted.